2011
DOI: 10.1093/nar/gkr1161
|View full text |Cite
|
Sign up to set email alerts
|

TarBase 6.0: capturing the exponential growth of miRNA targets with experimental support

Abstract: As the relevant literature and the number of experiments increase at a super linear rate, databases that curate and collect experimentally verified microRNA (miRNA) targets have gradually emerged. These databases attempt to provide efficient access to this wealth of experimental data, which is scattered in thousands of manuscripts. Aim of TarBase 6.0 (http://www.microrna.gr/tarbase) is to face this challenge by providing a significant increase of available miRNA targets derived from all contemporary experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
397
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 491 publications
(405 citation statements)
references
References 26 publications
(35 reference statements)
3
397
0
2
Order By: Relevance
“…In DIANA Lab's TarBase, only a correlation between miR-21 and MMP9 was found. The aforementioned analyses are current as of September 2014, and the list of miRNA databases is based on those used by Vergoulis et al (26).…”
Section: Discussionmentioning
confidence: 99%
“…In DIANA Lab's TarBase, only a correlation between miR-21 and MMP9 was found. The aforementioned analyses are current as of September 2014, and the list of miRNA databases is based on those used by Vergoulis et al (26).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in miR-let-7a might have negative effects on development of CRC. Caspase 3 (CASP3) is a validated target gene of miR-let-7a (Vergoulis et al 2012) as an effector of apoptosis, too. Tsang and Kwok (2008) could demonstrate an inverse interaction between miR-let7a and CASP3 in HepG2 and A431 cells, and Medina et al (1997) showed an induction of CASP3 activity by butyrate and TSA in Jurkat cells and LIM 1215 colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…DIANA-MicroT tools are being developed in Artemis Hatzigeorgiou's laboratory for over a decade (Kiriakidou et al, 2004;Sethupathy et al, 2006;Megraw et al, 2007;Maragkakis et al, 2009;Alexiou et al, 2010;Maragkakis et al, 2011;Reczko et al, 2011;Vergoulis et al, 2012;Vlachos et al, 2012;Paraskevopoulou et al, 2013a;Paraskevopoulou et al, 2013b;Paraskevopoulou et al, 2016). MicroT is specifically trained on a positive and a negative set of miRNA binding sites located in 3'-UTR and CDS regions.…”
Section: Targetscan (Http://wwwtargetscanorg/vert_71/)mentioning
confidence: 99%